Pengaruh Intensitas Mengikuti Suluk dan Kualitas Pelaksanaan Shalat Berjamaah Terhadap Akhlak Santri - Hani, Yesy Afrida; Yeli, Salmaini; Harun, Idris (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
Morals play an important role in Islam, reflected in the Koran and Hadith. Islamic boarding schools, such as the Babussalam Pekanbaru Islamic Boarding School, play a crucial role in shaping the morals of students through suluk, a spiritual journey to get closer to Allah SWT by cleansing oneself of negative traits and filling oneself with praiseworthy traits. Congregational prayer is also significant in strengthening the relationship with God and fostering good behavior. This research uses a quantitative approach to explore the correlation between the intensity of following suluk, the quality of congregational prayer, and the morals of the students. Data from 139 santri students showed that the intensity of suluk and the quality of congregational prayers had a significant positive effect on the morals of the students, with a percentage of 58.3% and the remaining 41.7% was influenced by other variables not discussed in this research. Despite this, some unethical behavior is still found among Islamic boarding school students, indicating the need to evaluate and improve religious education programs to ensure effectiveness in forming good morals.